A educação física no programa escolas interculturais de fronteira - Zotovici, Sandra Aparecida (2015)
The Intercultural Schools Program Frontier (PEIF) is an affirmative action implemented by the Ministry of Education (MEC), a native of public policy of the Federal Government and aims to promote regional integration through intercultural education caucione the integral formation of children and young people in border regions between Brazil and other countries. Its outbreak occurs by the action of teachers who are trained to join the faculty that will move between schools within the program in cities bordering the city of Foz do Iguaçu (Brazil), namely, Ciudad del Este (Paraguay) and Puerto Iguazu (Argentina). In this sense, the research aims to investigate the PEIF with a view to developing an educational project focused on the body and bodily practices that can support the actions of physical education teachers acting as trainers in schools this program. Specifically, we seek to: a) know the PEIF and guiding their training bases; b) monitor the PEIF implementation process in the border city of Foz do Iguaçu - PR, checking how the body and bodily practices themed appear in the Program; c) develop studies aimed to the body and bodily practices in intercultural perspective that can promote training activities with the PEIF; d) to propose policy actions by the PEIF, focused on the body and bodily intercultural practices, through the systematization of an educational proposal to guide physical education teachers acting as trainers in schools this program in the city of Foz do Iguaçu. The methodology is guided by theoretical nature study, whose foundation is based on bibliographic and documentary resources (especially related to MEC), plus descriptions resulting from ongoing researcher participation in training PEIF, informal conversations resulting from this course, as well as the data collected and the reflections on the analysis leads me to conclude that the contributions physical education can provide to border intercultural schools are related to dialogue with the humanities and social sciences, as well as the themed knowledge from body and body practices among the teachers to operate in PEIF, plus the knowledge of the participating schools and contact with teachers working in the program. So I return the need for interdisciplinary dialogue and reflection with the school community, to propose pedagogical intervention stocks of physical education with the PEIF that they can become guiding for the development of this program in the city of Foz do Iguaçu.